Frontispiece: Electrocatalytic Reduction of CO2 to Acetic Acid by a Molecular Manganese Corrole Complex. Issue 26 (15th June 2020) - De, Ratnadip; Gonglach, Sabrina; Paul, Shounik; Haas, Michael; Sreejith, S. S.; Gerschel, Philipp; Apfel, Ulf‐Peter; Vuong, Thanh Huyen; Rabeah, Jabor; Roy, Soumyajit; Schöfberger, Wolfgang
Abstract : CO2 Valorization In their Research Article on page 10527 ff., S. Roy, W. Schöfberger et al. demonstrate the electrocatalytic reduction of CO2 to acetic acid by a molecular manganese corrole complex, and propose the formation and reduction of an oxalate‐type intermediate.